Investigation of accuracy of rain-rate and rain-attenuation prediction models in satellite communications based on meteorological skills - BEHJATI, MEHRAN; MANDEEP, JIT SINGH; ISMAIL , MAHAMOD; NORDIN , ROSDIADEE (MAUSAM, 2017)
Rainfall is a major destructive factor which severely reduces the quality and reliability of propagated signals in satellite communications. Hence, rain-attenuation prediction plays a vital role in the satellite radio link planning and engineering. The accuracy of the rain-attenuation prediction models depends on two things; (i) the accuracy of rain-rate information and (ii) the area of study. Therefore, selecting an appropriate rain-attenuation prediction model for a new site without having any specific prediction model and experimental measured rain-rate would be challenging. In this regard, this letter takes advantage of climatology skills to find an accurate model for such kind of areas. To do so, we study the Urmia-site (37.55° N, 45.1° E) and its communication link with the Eutelsat 25A (25.5° E), where there is no available experimental measured data and specific prediction models for that site. Therefore, based on the meteorological skills, the Yong-in site in South-Korea (37.43° N, 126.93° E) was chosen, as a homogeneous area with Urmia, which has available measured data of rainfall and rain-attenuation. Afterward, the most common used global prediction models are applied to Yong-in and the results are compared with the existing measurements. Consequently, the more accurate rain-rate and rain-attenuation prediction models are investigated and generalized to Urmia, which are the ITU-R P.837-5 model with 34% r.m.s. and the Joo-Hwan model with 18% r.m.s., respectively. Finally, the amount of rain-attenuation in different useful frequency bands (10-50 GHz) is investigated for Urmia by the Joo-Hwan model.